2018
DOI: 10.1097/jpa.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Revolution: A Needs Assessment of Ultrasound Knowledge and Skills Among Graduating Physician Assistant Students

Abstract: Existing PA program curricula are insufficient for developing critical skills related to ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
1
13
0
2
Order By: Relevance
“…Despite PA students' desire for POCUS education, current medical school trends, and general clinical practice trends, few PA programs have successfully integrated POCUS education into their curricula. 3,4,6 Even with a majority of medical schools incorporating some amount of POCUS education into their curricula, very few have reported successful models of horizontal and vertical integration across the entirety of the curricula. 3,7 Barriers to incorporating POCUS into PA education are well described, with the top perceived barriers being lack of ultrasound machines, expense, and lack of faculty trained in POCUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite PA students' desire for POCUS education, current medical school trends, and general clinical practice trends, few PA programs have successfully integrated POCUS education into their curricula. 3,4,6 Even with a majority of medical schools incorporating some amount of POCUS education into their curricula, very few have reported successful models of horizontal and vertical integration across the entirety of the curricula. 3,7 Barriers to incorporating POCUS into PA education are well described, with the top perceived barriers being lack of ultrasound machines, expense, and lack of faculty trained in POCUS.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2018 survey of graduating physician assistant (PA) students, 82% of respondents desired formal POCUS training, and the same percentage of students believed that their POCUS education was insufficient to prepare them for clinical practice. 4 Yet, implementation of POCUS into the didactic education of PA students has been shown to be feasible and effective. 5 Still, although 68% of PA programs surveyed in 2019 believed POCUS skills should be taught in the didactic curriculum, only 11.2% of programs reported teaching these skills in their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound technicians require much more training relative to other types of radiologists, training which necessarily must include exposure to a wide variety of pathologies across a wide variety of patients in a format that enables dynamic investigation, historically in-person workshops, with the confluence of these factors resulting in fewer opportunities to receive this training. Indeed, a 2018 study found that 84% of the physician assistants surveyed believed that the training they received during their clinical rotations was insufficient preparation for clinical practice [43]. Among the many potential solutions to achieving sufficient ultrasonography expertise, increasing access to effective training opportunities via computer-based simulation platforms and developing automated image analysis systems to assist radiologists are two of the more promising areas.…”
Section: The Evolution Of Modern Segmentation Networkmentioning
confidence: 99%
“…7,9 Yet, in one study, 84% of PA students did not feel the instruction they had received on clinical rotations was sufficient to prepare them for clinical practice. 9…”
Section: Introductionmentioning
confidence: 99%
“…5,7 The majority of PA program directors think PA programs should teach hands-on US skills, 8 and the majority of PA students report an interest in learning how to use ultrasound. 7,9 Yet, in one study, 84% of PA students did not feel the instruction they had received on clinical rotations was sufficient to prepare them for clinical practice. 9 Barriers to adoption of US into PA programs include cost, lack of trained faculty members, and lack of time in academic schedules.…”
Section: Introductionmentioning
confidence: 99%